2012
DOI: 10.1186/1472-6955-11-20
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with reporting nursing errors in Iran: a qualitative study

Abstract: BackgroundReporting the professional errors for improving patient safety is considered essential not only in hospitals, but also in ambulatory care centers. Unfortunately, a great number of nurses, similar to most clinicians, do not report their errors. Therefore, the present study aimed to clarify the factors associated with reporting the nursing errors through the experiences of clinical nurses and nursing managers.MethodsA total of 115 nurses working in the hospitals and specialized clinics affiliated to Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
123
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(131 citation statements)
references
References 25 publications
6
123
0
2
Order By: Relevance
“…The findings of another study also showed that conscience is one the important modulators of Iranian nurses burnout (Rafii et al, 2004). Also, other Iranian study also found that conscience is an important factor for managing pain in patients by Iranian nurses (Hashemi et al, 2012). Conscience is an important concept for nurses.…”
Section: Discussionmentioning
confidence: 93%
“…The findings of another study also showed that conscience is one the important modulators of Iranian nurses burnout (Rafii et al, 2004). Also, other Iranian study also found that conscience is an important factor for managing pain in patients by Iranian nurses (Hashemi et al, 2012). Conscience is an important concept for nurses.…”
Section: Discussionmentioning
confidence: 93%
“…Consider also Hashemi (2012) in his study (Factors associated with reporting nursing errors in Iran) where he reported that the most common barriers preventing reporting the medical errors include: fear of legal action and job threats, fear of economic losses, fear of honor and dignity, weakness of knowledge and weakness of nursing skills in error management.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reasons cited were being unsure of what and how to report [1821], increased burden of effort for the HCPs [18], [19], [22], [23], organisational factors such as lack of feedback [21], [24], [25], blaming the individual instead of the system [14], [16], [17] and fear-related factors [13], [16], [26], [27]. …”
Section: Introductionmentioning
confidence: 99%